2021
DOI: 10.1002/adma.202104779
|View full text |Cite
|
Sign up to set email alerts
|

Cation‐Free siRNA Micelles as Effective Drug Delivery Platform and Potent RNAi Nanomedicines for Glioblastoma Therapy

Abstract: report of a versatile siRNA micelle platform for GBM treatment which can be potentially applied for the treatment of other brain disorders.Research data are not shared.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(50 citation statements)
references
References 63 publications
0
50
0
Order By: Relevance
“…Viral vectors and cationic nanoparticles not only have certain toxicity but also induce immunogenic responses. Furthermore, excessive cationic components readily cause decomposition of the carrier particles at the glomerular basement membrane, resulting in renal clearance of ncRNAs ( 175 ). Although scientific researchers have made great efforts to design a variety of promising noncationic nucleic acid carriers (octameric ribonucleoprotein, exosomes, spherical nucleic acids and siRNA conjugates) to load ncRNAs ( 183 , 184 ), viral vectors and cationic nanoparticles are still the most commonly used delivery methods in ncRNA therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Viral vectors and cationic nanoparticles not only have certain toxicity but also induce immunogenic responses. Furthermore, excessive cationic components readily cause decomposition of the carrier particles at the glomerular basement membrane, resulting in renal clearance of ncRNAs ( 175 ). Although scientific researchers have made great efforts to design a variety of promising noncationic nucleic acid carriers (octameric ribonucleoprotein, exosomes, spherical nucleic acids and siRNA conjugates) to load ncRNAs ( 183 , 184 ), viral vectors and cationic nanoparticles are still the most commonly used delivery methods in ncRNA therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Nanoparticles with addition of the Ang polypeptide possess obvious brain targeting characteristics and do not destroy the integrity of the BBB. However, the targeting effect of Ang polypeptide modification is ineffective in normal glial cells with LRP-1 deficiency ( 175 ). Mahmoudi et al ( 176 ) attempted to use arginine-glycine-aspartate (RGD) peptide-modified liposomes as delivery carriers of curcumin for the targeted treatment of glioma.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…For GBM therapy, RNA interference (RNAi) therapy can specifically suppress GBM growth through silencing oncogene expression with high efficacy, negligible toxicity, and low-dose requirements. [27,28] Transglutaminase 2 (TG2), a multifunctional enzyme that is widely distributed in human bodies, was best known for its Ca 2+ -dependent catalytic crosslinking of proteins through ε-(γ-glutamyl)-lysine isopeptide bonds. [29,30] With a more profound understanding of cancers, several studies have established it as a validated biomarker for GBM, [31][32][33] which was overexpressed in GBM and the aberrant expression level was associated with cancer progression.…”
Section: Introductionmentioning
confidence: 99%
“…However, challenges for siRNA therapeutics lie in the effective delivery and enhancing the treatment effects [18]. Emerging studies have demonstrated that novel nanotechbased strategies can robustly enhance drug and siRNA delivery, which offers synergetic treatment potentials for multiple diseases [19][20][21][22][23][24]. Cationic polymeric vectors are the most studied siRNA delivery vectors [25].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, difficulties, such as high cytotoxicity, low transfection efficiency, and uncontrollable and untraceable gene transfer, still hamper its progression into clinical applications of gene therapy [26]. The high cytotoxicity of a cationic vector is generally attributed to the plentiful positive charge and non-biodegradable accumulation of the vector [21,27]. Low delivery efficiency and poor vector unpacking are the major limiting steps for high-performance gene delivery.…”
Section: Introductionmentioning
confidence: 99%